Lyophilization of Molecular Biology Reactions: A Review - Prado, Nayra O.; Lalli, Larissa Araújo; Blanes, Lucas; Zanette, Dalila Lucíola; Aoki, Mateus Nóbrega (Mini Reviews in Medicinal Chemistry, 2023)
Molecular biology is a widely used and widespread technique in research and as a laboratory diagnostic tool, aiming to investigate targets of interest from the obtainment, identification, and analysis of genetic material. In this context, methods, such as Polymerase Chain Reaction (PCR), Reverse Transcription Polymerase Chain Reaction (RT-PCR), real-time PCR, loopmediated isothermal amplification (LAMP), and loop-mediated isothermal amplification with reverse transcription (RT-LAMP), can be cited. Such methods use enzymes, buffers, and thermosensitive reagents, which require specific storage conditions. In an attempt to solve this problem, the lyophilization procedure (dehydration process by sublimation) can be applied, aiming to preserve and prolong the useful life of the reaction components in cases of temperature variation. In this review, we present a synthesis of the lyophilization process, describing the events of each step of the procedure and providing general information about the technique. Moreover, we selected lyophilization protocols found in the literature, paying attention to the conditions chosen by the authors for each step of the procedure, and structured the main data in tables, facilitating access to information for researchers who need material to produce new functional protocols.
Keywords: pointof- care